PENGARUH EDUKASI DAN HOMECARE OLEH FARMASIS TERHADAP PENGETAHUAN DAN KEPATUHAN PASIEN DIABETES MELITUS TIPE 2 - vony nofrika; syamsuddin syamsuddin; Sesilia A Keban (Farmasains : Jurnal Ilmiah Ilmu Kefarmasian, 2016)
Increased knowledge and compliance of type 2 DM patient should be supported by the pharmaceutical services in the form of education and homecare. The purpose of this research to determine the effect of the implementation of pharmacists services in improving the knowledge and compliance of type 2 DM patient so that blood sugar levels can be controlled properly. this research is a prospective, quasi-experimental methods nonequivalent control group design. Respondents were 108 people divided into 3 groups of intervention namely the control group, the intervention group I conducted Education twice by using booklet media, and the second intervention group was educated and homecare pharmacist respectively twice. The results showed that the average value of knowledge and compliance in the intervention group I showed an increase from 68.81 to 70.06 and 2.01 to 0.38. While in the intervention group II there was an increase from 66 to 72,34 and 3,97 to 0,14. GDPP levels before the intervention included poorly controlled categories turned to moderate control after intervention II.